A Cryogenically Flexible Covalent Organic Framework for Efficient Hydrogen Isotope Separation by Quantum Sieving1. Issue 50 (11th November 2013) - Oh, Hyunchul; Kalidindi, Suresh Babu; Um, Youngje; Bureekaew, Sareeya; Schmid, Rochus; Fischer, Roland A.; Hirscher, Michael
<x xml:space="preserve">Abstract</x> Pyrdine incorporation into the covalent organic framework COF‐1 resulted in a highly dense packing structure in which the pyridine occupies the hexagonal pore space between the COF layers. This optimizes pore aperture for quantum sieving of hydrogen isotopes and introduces flexibility at cryogenic temperatures into the system. The separation factor (S<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg4t3kjnqg" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> D 2/H 2</alternatives>) is about 10 at 22 K, which is the highest reported to date.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>